2015
DOI: 10.1128/jb.00186-15
|View full text |Cite
|
Sign up to set email alerts
|

Immunogold Localization of Key Metabolic Enzymes in the Anammoxosome and on the Tubule-Like Structures of Kuenenia stuttgartiensis

Abstract: Anaerobic ammonium-oxidizing (anammox) bacteria oxidize ammonium with nitrite as the terminal electron acceptor to form dinitrogen gas in the absence of oxygen. Anammox bacteria have a compartmentalized cell plan with a central membrane-bound "prokaryotic organelle" called the anammoxosome. The anammoxosome occupies most of the cell volume, has a curved membrane, and contains conspicuous tubule-like structures of unknown identity and function. It was suggested previously that the catalytic reactions of the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 37 publications
1
33
1
Order By: Relevance
“…Thus, the differences in isotope effects may reflect the NxrA phylogeny. However, anammox-bacteria oxidize nitrite in the anammoxosome (de Almeida et al 2015) with an inverse isotope effect of about 31 ‰ (Brunner et al 2013), which is much more pronounced than what we found in Nitrospina and Nitrospira. Indeed, the previously determined isotope effects of Nitro bacter and Nitrococcus are apparently more pronounced and thus closer to that of anammox bacteria.…”
Section: Inverse Kinetic Isotope Effects During Nitrite Oxidationcontrasting
confidence: 52%
“…Thus, the differences in isotope effects may reflect the NxrA phylogeny. However, anammox-bacteria oxidize nitrite in the anammoxosome (de Almeida et al 2015) with an inverse isotope effect of about 31 ‰ (Brunner et al 2013), which is much more pronounced than what we found in Nitrospina and Nitrospira. Indeed, the previously determined isotope effects of Nitro bacter and Nitrococcus are apparently more pronounced and thus closer to that of anammox bacteria.…”
Section: Inverse Kinetic Isotope Effects During Nitrite Oxidationcontrasting
confidence: 52%
“…S1). Cleavage of the N-terminal leader sequence (32 amino acids) would facilitate export of HDH into the anammoxosome, an anammox-specific cell organelle where catabolism resides and where processed HDH is specifically localized as recently shown by immunogold labelling (16).…”
Section: Resultsmentioning
confidence: 94%
“…S9). Based on the known cell biology ( 64 ), biochemistry and anammox metabolism ( 4, 65, 66 ), and the expression profiles of the known anammox pathways obtained with the differential expression analysis done in this study (Table S3 and 4), we propose a putative molecular model to describe how electrons flow from the anammoxosome to the electrode in the EET-dependent anammox process (Fig. S10).…”
Section: Supplementary Materialsmentioning
confidence: 99%